Athletic Games for The Motion of Children with Spesial Needs: a Literatur Review - Arif Budiman; Atrup Atrup; Hendra Mashuri (Universitas STRADA Indonesia, 2020)
Children with special needs (ABK) tend to be passive, because they have physical or mental deficiencies. In addition, people with special needs have problems in the psychomotor domain as a result of limitations in sensomotor abilities and limitations in learning abilities. Literature review using the method used is through a journal search system on google with the keywords athletic games on the motion of children with special needs. Journals and thesis used as literature have full text inclusion criteria, the subject is a child with special needs, the type of journal is the journal for the past 6 years. Based on the results of the review it was found that there are various kinds of athletic games to the motion of children with special needs. Literartur review conclusions that with a variety of athletic games can affect the motion of children with special needs